1997
DOI: 10.1104/pp.115.4.1569
|View full text |Cite
|
Sign up to set email alerts
|

Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase Activase Deficiency Delays Senescence of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase but Progressively Impairs Its Catalysis during Tobacco Leaf Development

Abstract: Transgenic tobacco (Nicofiana fabacum L. cv W38) plants with an antisense gene directed against the mRNA of ribulose-1,sbiphosphate carboxylase/oxygenase (Rubisco) activase grew more slowly than wild-type plants in a C0,-enriched atmosphere, but eventually attained the same height and number of leaves. Compared with the wild type, the anti-activase plants had reduced CO, assimilation rates, normal contents of chlorophyll and soluble leaf protein, and much higher Rubisco contents, particularly in older leaves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 35 publications
(60 reference statements)
4
48
0
Order By: Relevance
“…8). Interestingly, in transgenic plants with reduced Rubisco activity due to decreased expression of Rubisco activase, the senescence-related degradation of Rubisco is delayed relative to chlorophyll and other soluble proteins (He et al 1997). Presumably, the persistence of large amounts of Rubisco late into leaf development is a consequence of the reduced carbamylation of the Rubisco pool (He et al 1997); a similar mechanism may be involved in the age-related accumulation of Rubisco in evergreen leaves.…”
Section: Co 2 Supply Versus the Chloroplastic Co 2 Operating Pointmentioning
confidence: 99%
“…8). Interestingly, in transgenic plants with reduced Rubisco activity due to decreased expression of Rubisco activase, the senescence-related degradation of Rubisco is delayed relative to chlorophyll and other soluble proteins (He et al 1997). Presumably, the persistence of large amounts of Rubisco late into leaf development is a consequence of the reduced carbamylation of the Rubisco pool (He et al 1997); a similar mechanism may be involved in the age-related accumulation of Rubisco in evergreen leaves.…”
Section: Co 2 Supply Versus the Chloroplastic Co 2 Operating Pointmentioning
confidence: 99%
“…He et al (1997) have shown that silencing RCA increases RuBPCase content in cultivated tobacco. In order to determine if silencing RCA and RuBPCase influences the accumulation of large subunits of RuBPCase in N. attenuata, we performed a one-dimensional protein analysis of EV, irRCA, and asRUB plants (Fig.…”
Section: Rubpcase Levelsmentioning
confidence: 99%
“…The degradation and remobilization of the soluble proteins provide an important source of N and sulfur for the other parts of the developing plants (Friedrich and Huffaker, 1980). However, RuBPCase declines faster than RCA (He et al, 1997). Therefore, despite having less RuBPCase, asRUB plants have similar photosynthetic rates as EV plants.…”
mentioning
confidence: 99%
See 2 more Smart Citations